Interaction of fibrinogen–magnetic nanoparticle bioconjugates with integrin reconstituted into artificial membranes. Issue 38 (28th September 2020) - Martens, Ulrike; Janke, Una; Möller, Sophie; Talbot, Delphine; Abou-Hassan, Ali; Delcea, Mihaela
Abstract : Fibrinogen provides colloidal stability to maghemite NPs and fibrinogen–NP bioconjugates interact with integrin-containing artificial membranes as model system for platelets. Abstract : Magnetic nanoparticles have a broad spectrum of biomedical applications including cell separation, diagnostics and therapy. One key issue is little explored: how do the engineered nanoparticles interact with blood components after injection? The formation of bioconjugates in the bloodstream and subsequent reactions are potentially toxic due to the ability to induce an immune response. The understanding of the underlying processes is of major relevance to design not only efficient, but also safe nanoparticles for e.g. targeted drug delivery applications. In this study, we report on maghemite nanoparticles functionalized with citrate-, dextran- and polyethylene glycol coatings and their interaction with the clotting protein fibrinogen. Further, we investigate using biophysical tools ( e.g. dynamic light scattering, circular dichroism spectroscopy and quartz crystal microbalance) the interaction of the magnetic nanoparticles–fibrinogen bioconjugates with artificial cell membranes as a model system for blood platelets. We found that fibrinogen corona formation provides colloidal stability to maghemite nanoparticles. In addition, bioconjugates of fibrinogen with dextran- and citrate-coated NPs interact with integrin-containing lipid bilayer, especially upon treatment with divalent ions, whereas PEG-coating reveals minor interaction. Our study at the interface of protein-conjugated nanoparticles and artificial cell membranes is essential for engineering safe nanoparticles for drug delivery applications.